A demographic scenario of an urban area: A study of selected population characteristics of Tamluk municipality in East Medinipur district, West Bengal - Balai Adhikary,; Monisha Jana,; Santu Guchhait,; Suman Dinda,; Susmita Maity,; Sayantan Maity, (National Geographical Journal of India, 2023)
Demographic characteristic reveals the socioeconomic condition of society. It includes distribution, sex ratio, child (0-6 years) sex ratio, works participation of the population, and literacy. Intra-municipality variation in population characteristics is noticeable in Tamluk municipality of the East Medinipur district of West Bengal in eastern India. The present paper attempts to study the intra-municipality variation in demographic characteristics and measure the gender disparity in literacy and level of development in the municipality area. Based on the Census of India 2011 database, population density, average urban household size, sex ratio, child (0-6 years) sex ratio, and male and female literacy is analyzed. Descriptive statistics and gender disparity in literacy are measured using the disparity index (Kundu and Rao,1986). Many of the urban pockets in the municipality have a population under poor socioeconomic conditions. Several wards show a gender gap in work participation. There is a negative change in the sex ratio and child sex ratio. The average percentage share of the slum population to the total population has immensely increased. A large percentage of the urban population in Tamluk municipality shows a poor state.